PUBLIC SERVICE IN THE PERSPECTIVE OF GOVERNMENT ETHICS IN SAMOFA DISTRICT, BIAK NUMFOR REGENCY - NIKMAH, LAILA AINUN; JAFAR, JIBRAN; RAYAR, LAURENCE (Gema Kampus IISIP YAPIS Biak, 2025)
This study aims to evaluate public services from the perspective of government ethics in Samofa District, Biak Numfor Regency. High-quality public services reflect the state's commitment to its citizens, and are an indicator of the implementation of good governance principles. However, initial findings indicate a number of problems, such as low discipline of civil servants, lack of responsibility in carrying out tasks, and less than optimal quality of interaction between employees and the community. This study uses a qualitative descriptive approach, with data collection methods in the form of observation, in-depth interviews, and documentation. The formal focus of the study includes public service systems and policies, while the material focus includes civil servant behavior, organizational culture, and the application of ethical values ​​in the service process. The research findings indicate that public services in Samofa District still experience significant obstacles, especially in terms of employee discipline and professionalism. Problems such as late attendance, lack of training on ethics, and limited facilities and incentives are the main causes of the decline in service quality. However, there is an initiative from the district leadership to foster a constructive work culture and maintain public trust. This study recommends increasing the capacity of civil servants through training based on government ethics, strengthening internal monitoring mechanisms, and providing proportional and fair incentives. These efforts are expected to encourage improvements in the quality of public services, both in terms of administration and morals, by placing the interests of the community as the main priority.